2021
DOI: 10.21608/asejaiqjsae.2021.181204
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina as Anti-Obesity and Hepato-Renal Protective Agent in MSG -Exposed Female Rats

Abstract: High intake of monosodium glutamate (MSG)containing foods was reported as a major health problem in Egypt. Thus, dietary interventions aim to prevent the deleterious effects of this additive were badly needed. This study was carried out to investigate the effect of concurrent consumption of MSG and Spirulina (S. platensis) on body weight as well as hepato-renal functions and histopathology in female rats. Twenty adult female albino rats were divided into four equal groups, including the control group, while gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Khalifa et al [26] also found a significant decrease in the levels of ALT and AST in goats treated with SP. El-Hashash [25] also reported that the level of ALT and AST enzymes decreased to normal range when using SP for six weeks. In a study on mice, it showed a significant decrease in level of enzymes ALT and AST in blood serum of those with osteoporosis when treated with SP at 6% of the feed for 60 days [27].…”
Section: Alanine Aminotransferase (Alt)mentioning
confidence: 92%
See 1 more Smart Citation
“…Khalifa et al [26] also found a significant decrease in the levels of ALT and AST in goats treated with SP. El-Hashash [25] also reported that the level of ALT and AST enzymes decreased to normal range when using SP for six weeks. In a study on mice, it showed a significant decrease in level of enzymes ALT and AST in blood serum of those with osteoporosis when treated with SP at 6% of the feed for 60 days [27].…”
Section: Alanine Aminotransferase (Alt)mentioning
confidence: 92%
“…These results agreed with the study of Mansour and Zeitoun [16] where they found a significant effect on the level of AST of SP treatments compared to the control treatment. On the other hand, there was a study by [22,25] who indicated that SP supplements led to a decrease in level of ALT and AST in blood serum of different breeds of sheep. Khalifa et al [26] also found a significant decrease in the levels of ALT and AST in goats treated with SP.…”
Section: Alanine Aminotransferase (Alt)mentioning
confidence: 99%